Effect of the recovery duration of a repeated sprint exercise on the power output, jumping performance and lactate concentration in pre-pubescent soccer players - Nikolaidis, P. T.; Knechtle, B. (Biomedical Human Kinetics, 2016)
Study aim: The aim of the present study was to examine the effect of two different recovery durations (2 min versus 5 min) on the physiological responses (power output, stretch-shortening cycle and lactate concentration) to a 5×6 s repeated cycling sprint exercise protocol in pre-pubescent soccer players.